The Influence of Macroeconomic Variables on Non-Performing Finance in Sharia Commercial Banks - Salim, Agus; Zakiyah, Annisa Eka; Nabilah, Rifda Syahda; Kirana, Marshanda Tisa; Dewanti, Citra Purnama (Universitas Darussalam Gontor, 2024)
One of the advantages of the sharia banking business is financing productive sectors that do not contain haram elements. Financing in the micro, small and medium sectors is a sharia banking financing business line, but there is a big risk of bad credit. In recent years, increasing global and domestic economic uncertainty has led to depreciation of the exchange rate, unstable prices of basic commodities, thereby reducing people's purchasing power. This research aims to examine macroeconomic variables such as the exchange rate, inflation and production index as a proxy for GDP towards NPF of sharia banking. The research uses monthly time-series data and the OLS method. The research results show that macroeconomic variables have an influence on NPF. The research implication is that the stability of macroeconomic conditions can maintain people's purchasing power which can influence the NPF level of sharia banking.